PENGARUH PEMBERIAN AROMA TERAPI LEMON ELEKTRIK TERHADAP MUAL DAN MUNTAH PADA IBU HAMIL TRIMESTER I - Detty Afriyanti; Nurul Huda Rahendza (Universitas Fort de Kock Bukittinggi, 2020)
Nausea and vomiting in pregnancy are the most common conditions of pregnancy women, it happens between 5 to 8 pregnancy weeks . The aim of this study was to determine The Effectiveness of Aroma Electric Lemon Therapy toward Nausea and Vomiting of the First Trimester Pregnant Women in BPM